Edukasi Bahaya Penyalahgunaan Narkotika, Psikotropika, Dan Zat Adiktif Dan Pentingnya Kesehatan Reproduksi Bagi Remaja - Mahfudzah, Nur Arifah; Rahayu, Amelia Putri; Fitria, Fitria; Ridha, Ridha Amelia; Serang, Aditya Anugerah F; Stevani, Hendra; Dewi, Ratnasari (Jurusan Farmasi Politeknik Kesehatan Makassar, 2024)
EducationOntheDangersofDrugAbuseandTheImportanceOfReproductiveHealthFor AdolescentsBackground, Adolescence is a transitional phase that is vulnerable to drug abuse and low awareness of reproductive health, which risks causing serious impacts. With the existence of health counseling which aims to improve students' understanding of the dangers of drug abuse and the importance of reproductive health for adolescents. Methods, interactive education sessions with presentations, and question and answer sessions to strengthen understanding. Results, this activity was attended by 29 students with 11 male students and 18 female students in class VIII UPT SMP Negeri 07 Makassar. There was an increase in student understanding from the results of the questionnaire which was originally for the